Elliptical ultrasonic–assisted turning tool with longitudinal and bending vibration modes. (June 2017) - Amini, Saeid; Khosrojerdi, MR; Nosouhi, Reza
Ultrasonic-assisted turning is a machining process in which a vibrational displacement (usually in ultrasonic frequencies) is superimposed with the machining displacements in the cutting direction (one-dimensional ultrasonic-assisted turning) or in the cutting direction along with the radial direction (two-dimensional ultrasonic-assisted turning or elliptical ultrasonic–assisted turning). In this research, an elliptical ultrasonic–assisted turning tool is designed in ABAQUS software, in which the longitudinal and bending vibration modes have the minimum resonance frequency difference, so that the resonance of both the vibration modes can be achieved in a definite frequency. A set of half-ring piezoelectric stacks is employed for excitement of the bending mode, and a set of ring-shaped piezoelectric stacks is used for the excitement of the longitudinal mode. There is a phase shift with the amount of π/2 between the longitudinal and bending vibration modes to produce an elliptical vibration. The manufactured tool is employed for machining of copper, which resulted in better surface finish and lower cutting forces.